2022
DOI: 10.3390/cancers14184524
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA hsa_circ_0062682 Binds to YBX1 and Promotes Oncogenesis in Hepatocellular Carcinoma

Abstract: Circular RNAs (circRNAs) have been shown to play an important role in the pathogenesis of hepatocellular carcinoma (HCC). By implementing available transcriptomic analyses of HCC patients, we identified an upregulated circRNA hsa_circ_0062682. Stable perturbations of hsa_circ_0062682 in Huh-7 and SNU-449 cell lines influenced colony formation, migration, cell proliferation, sorafenib sensitivity, and additionally induced morphological changes in cell lines, indicating an important role of hsa_circ_0062682 in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…[16] As a multifaceted molecule, YBX1 functions as a transcription factor when located in the nucleus, [17] whereas it typically serves as an RNA-binding protein in the cytoplasm. [10] Numerous studies have reported that YBX1 promotes tumor growth and metastasis in various cancer types including HCC, [8,18] colorectal cancer, [9] and clear cell renal cell carcinoma. [11] Notably, Chen et al demonstrated a novel role of YBX1 in stabilizing the heparin-binding growth factor (HDGF) mRNA by targeting the m5C-modified site in bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] As a multifaceted molecule, YBX1 functions as a transcription factor when located in the nucleus, [17] whereas it typically serves as an RNA-binding protein in the cytoplasm. [10] Numerous studies have reported that YBX1 promotes tumor growth and metastasis in various cancer types including HCC, [8,18] colorectal cancer, [9] and clear cell renal cell carcinoma. [11] Notably, Chen et al demonstrated a novel role of YBX1 in stabilizing the heparin-binding growth factor (HDGF) mRNA by targeting the m5C-modified site in bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It modulates the stability of target transcripts by recognizing the m5C modification. [ 7a ] Previous studies have demonstrated the oncogenic function of YBX1 as an RNA‐binding protein in tumorigenesis and cancer metastasis such as hepatocellular carcinoma (HCC), [ 8 ] colorectal cancer, [ 9 ] Chronic myeloid leukemia [ 10 ] and clear cell renal cell carcinoma. [ 11 ] Recently, increasing evidence has demonstrated that YBX1 functions as an m5C reader in bladder, [ 7a ] breast, [ 12 ] and gynecologic cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Razpotnik et al identified an upregulated circRNA, hsa_circ_0062682, that could interact with YBX1 in hepatocellular carcinoma. Knockdown of hsa_circ_0062682 revealed the transcription factors E2F1, Sp1, HIF-1α, and NFκB1 as potential downstream targets [ 44 ]. However, this study did not explore the relationship between YBX1 and E2F1.…”
Section: Discussionmentioning
confidence: 99%
“…The YBX1 protein was identified to bind with circ_0062682. However, the precise downstream molecular mechanisms of this circ_0062682 and YBX1 interplay on HCC progression remain a subject warranting further exploration [ 130 ].…”
Section: Ncrnas Regulate Methylation-related Proteins In Hccmentioning
confidence: 99%